Dietary cholesterol promotes steatohepatitis related hepatocellular carcinoma through dysregulated metabolism and calcium signaling. Issue 1 (December 2018) - Liang, Jessie; Teoh, Narcissus; Xu, Lixia; Pok, Sharon; Li, Xiangchun; Chu, Eagle; Chiu, Jonathan; Dong, Ling; Arfianti, Evi; Haigh, W.; Yeh, Matthew; Ioannou, George; et al.
Abstract The underlining mechanisms of dietary cholesterol and nonalcoholic steatohepatitis (NASH) in contributing to hepatocellular carcinoma (HCC) remain undefined. Here we demonstrated that high-fat-non-cholesterol-fed mice developed simple steatosis, whilst high-fat-high-cholesterol-fed mice developed NASH. Moreover, dietary cholesterol induced larger and more numerous NASH-HCCs than non-cholesterol-induced steatosis-HCCs in diethylnitrosamine-treated mice. NASH-HCCs displayed significantly more aberrant gene expression-enriched signaling pathways and more non-synonymous somatic mutations than steatosis-HCCs (335 ± 84/samplevs 43 ± 13/sample). Integrated genetic and expressional alterations in NASH-HCCs affected distinct genes pertinent to five pathways: calcium, insulin, cell adhesion, axon guidance and metabolism. Some of the novel aberrant gene expression, mutations and core oncogenic pathways identified in cholesterol-associated NASH-HCCs in mice were confirmed in human NASH-HCCs, which included metabolism-related genes (ALDH18A1, CAD, CHKA, POLD4, PSPH and SQLE ) and recurrently mutated genes (RYR1, MTOR, SDK1, CACNA1H  andRYR2) . These findings add insights into the link of cholesterol to NASH and NASH-HCC and provide potential therapeutic targets. Nonalcoholic steatohepatitis (NASH) and dietary cholesterol are risk factors for hepatocellular carcinoma (HCC). Here, the authors utilise mouse models to show that dietary cholesterol induces NASH by deregulating genes involved in metabolism, inflammation and calcium signaling to induce NASH-HCC.